2010
DOI: 10.3892/or_00000918
|View full text |Cite
|
Sign up to set email alerts
|

Significant elevation of CLDN16 and HAPLN3 gene expression in human breast cancer

Abstract: Abstract. Cancer development involves the destruction of tight junctions, deprivation of cell polarity, and increased cell mobility. Claudin 16 (CLDN16) is a tight junction protein and plays important roles in the maintenance of cell polarity, cellular arrangement, adhesion, paracellular transport, and ionic permeability of various epithelia. A novel link protein, HAPLN3, functions in hyaluronic acid binding and cell adhesion. Both genes are hypothesized to be related to cancer development and metastasis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Our study identified 7 DMP-associated genes that could be a DNA methylation signature for determining high-grade and aggressive EOC. Of these 7 DMP-associated genes, hypomethylated CLDN16 is a member of the claudin family modulating cell polarity and is also a biomarker of breast cancer aggressiveness [ 55 ]. Additionally, hypermethylated LZTFL1 has been reported to be involved in maintaining cell differentiation [ 56 ], ABHD2 was found to control anoikis resistance in HGSOC [ 57 ], RNF144A was shown to be a tumor suppressor in governing breast cancer growth and metastasis [ 58 ], and HPS4 was shown to alter the functions of the small GTPases Rab32 and Rab38, which are associated with the recurrence of lung cancer [ 59 ], 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified 7 DMP-associated genes that could be a DNA methylation signature for determining high-grade and aggressive EOC. Of these 7 DMP-associated genes, hypomethylated CLDN16 is a member of the claudin family modulating cell polarity and is also a biomarker of breast cancer aggressiveness [ 55 ]. Additionally, hypermethylated LZTFL1 has been reported to be involved in maintaining cell differentiation [ 56 ], ABHD2 was found to control anoikis resistance in HGSOC [ 57 ], RNF144A was shown to be a tumor suppressor in governing breast cancer growth and metastasis [ 58 ], and HPS4 was shown to alter the functions of the small GTPases Rab32 and Rab38, which are associated with the recurrence of lung cancer [ 59 ], 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the expression of HAPLN3 was shown to be significantly higher in breast cancer tissues compared to the normal breast tissues. It was associated with the metabolism dysregulation, mobility, and migration of cancer cells in TNBC (42,43). These imply the value of MFGE8-HAPLN3 in guiding diagnosis and treatment choices in cancer.…”
Section: Discussionmentioning
confidence: 93%
“…HAPLN3 has been reported to play an important role in maintaining the stability of the extracellular matrix, thereby regulating the mobility and migration of tumor cells. Kuo et al (2010) found that HAPLN3 was significantly overexpressed in breast cancer tissues, but there was no correlation between HAPLN3 gene expression and overall survival. Ubiquinol cytochrome c reductase (UQCRFS1, also named as Rieske Fe-S protein) is a catalytic submit of complex III and plays an important role in the mitochondrial respiratory chain.…”
Section: Discussionmentioning
confidence: 94%